Gaudí : architect of imagination - Katz, Susan B., 1971- (NorthSouth, 2022)
A biography of Catalan architect Antoni Gaudí, known for his inventive and flamboyant style, from his colorful mosaics and unprecedented facades to his playful forms and bold buildings that make Barcelona shine.